SEMI-CORE STATES: A NEW CATEGORY FOR RETHINKING THE STRUCTURE OF POWER - Morales Ruvalcaba, Daniel (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
Do all the core states occupy identical positions in the hierarchy of world power and perform the same functions? The hypothesis outlined here is that there is an unforeseen category: semi-core states. They have very important socio-institutional power but are “tertiary” in terms of economic-military and communicative-cultural power. Despite their relative marginality, they play strategic roles in international politics, especially in support of the central powers (great and middle). This article analyzes the general characteristics of the so-called center of the world-system, identifies the semi-core states theoretically and empirically, explores their genesis and analyzes their roles in the international system.